Association between maternal rectovaginal group B streptococcus and the risk of stillbirth: a meta-analysis - Yujue Wang; Jingjing Liu; Jinlian Song; Teng Zhang (PeerJ)
Background Group B streptococcus (GBS) colonization in pregnant women is associated with adverse perinatal outcomes, including stillbirth. This meta-analysis investigated the relationship between maternal rectovaginal GBS colonization and the risk of stillbirth. Methods We conducted a comprehensive literature search across several databases, including PubMed, Embase, Web of Science, Wanfang, and China National Knowledge Infrastructure, covering studies published from the inception of the database until September 9, 2024. The search focused on observational studies comparing the risk of stillbirth in pregnant women with and without rectovaginal GBS colonization. Results were summarized using odds ratios (ORs) and 95% confidence intervals (CIs), and a random-effects model was used to account for potential heterogeneity. Results A total of ten studies comprising 121,195 pregnant women were included in the analysis. The pooled results indicated no significant overall association between maternal rectovaginal GBS colonization and the risk of stillbirth (OR: 1.66, 95% CI [0.95–2.91], p = 0.08; I2 = 84%). However, sensitivity analyses revealed a significant association in studies that included intrapartum antibiotic prophylaxis (IAP) (OR: 1.36, 95% CI [1.02–1.80], p = 0.03). Subgroup analyses demonstrated a significant association between maternal rectovaginal GBS colonization and stillbirth risk in retrospective studies (OR: 2.62, p = 0.04) and in studies employing multivariate analysis (OR: 2.11, p = 0.04). Conclusions While the meta-analysis did not find a significant overall association between maternal rectovaginal GBS colonization and stillbirth, significant associations were noted under specific conditions, such as studies using IAP, retrospective designs, and multivariate analyses. Further research is needed to clarify these associations.